Search for vectorlike leptons in multilepton final states in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; Fruehwirth,R; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2019)
A search for vectorlike leptons in multilepton final states is presented. The data sample corresponds to anintegrated luminosity of 77.4 fb−1 of proton-proton collisions at a center-of-mass energy of 13 TeVcollected by the CMS experiment at the LHC in 2016 and 2017. Events are categorized by the multiplicityof electrons, muons, and hadronically decaying τ leptons. The missing transverse momentum and the scalarsum of the lepton transverse momenta are used to distinguish the signal from background. The observedresults are consistent with the expectations from the standard model hypothesis. The existence of avectorlike lepton doublet, coupling to the third-generation standard model leptons in the mass range of120–790 GeV, is excluded at 95% confidence level. These are the most stringent limits yet on theproduction of a vectorlike lepton doublet, coupling to the third-generation standard model leptons.